Laryngeal cancer mortality trends in European countries. Issue 4 (14th September 2015) - Chatenoud, Liliane; Garavello, Werner; Pagan, Eleonora; Bertuccio, Paola; Gallus, Silvano; La Vecchia, Carlo; Negri, Eva; Bosetti, Cristina
Abstract : After a steady increase between the 1950s and the 1970s, laryngeal cancer mortality has been levelling off since the early 1980s in men from most western and southern European countries and since the early 1990s in central and eastern Europe. To update trends in laryngeal cancer mortality, we analyzed data provided by the World Health Organization over the last two decades for 34 European countries and the European Union (EU) as a whole. For major European countries, we also identified significant changes in trends between 1980 and 2012 using joinpoint regression analysis. Male mortality in the EU was approximately constant between 1980 and 1991 (annual percent change, APC=−0.5%) and declined by 3.3% per year in 1991–2012. EU age‐standardized (world population) rates were 4.7/100, 000 in 1990–91 and 2.5/100, 000 in 2010–2011. Rates declined in most European countries, particularly over the last two decades. In 2010–11, the highest male rates were in Hungary, the Republic of Moldova, and Romania (over 6/100, 000), and the lowest ones in Finland, Norway, Sweden, and Switzerland (below 1/100, 000). In EU women, mortality was stable around 0.29/100, 000 between 1980 and 1994 and slightly decreased thereafter (APC=−1.3%; 0.23/100, 000 in 2000–01). We also considered male incidence trends for nine European countries or cancer registration areas. In most of them, declines were observed over recent decades. Laryngeal cancer mortality thus showed favourable trends over the last few decades in most Europe, following favourable changes in tobacco and, mostly for Mediterranean countries, alcohol consumption. Abstract : What's new? The study quantifies the favourable trends of laryngeal cancer mortality in most European countries over the last few decades, following reduction in tobacco and, for Mediterranean countries, alcohol consumption.